Tropical Eczema - A New Entity - Nirmala Devi P; Sentamilselvi G; Janaki C; Janaki V.R (Wolters Kluwer Medknow Publications, 2000)
A new entity named as tropical eczema has been described in patients uniquely presenting with pruritic, papulovesicular rash in summer months, the majority of whom was female in the middle age group. Morphologically, the lesions varied from erythermatous, moist, excoriated papules and papulovesicular dry, scaly, flattened papules and patches which chiefly involved the flexural areas, though others like arms, thighs and trunk were also additionally involved in many patients. Though the clinical picture resembled Groverâ€s disease (transient acantholytic dermatosis) in many aspects, the age group, the sex and the sites of chronic dermatitis with no evidence of acantholysis or dyskeratosis. Hence, this dermatosis has been labeled as â€TROPICAL ECZEMAâ€ for its occurrence in tropical climate with classical eczematous histology.